2013
DOI: 10.1080/00131911.2013.768601
|View full text |Cite
|
Sign up to set email alerts
|

How might teachers enable learner self-confidence? A review study

Abstract: In the context of learner-centred learning and curricular reform, self-confidence is invoked as an important construct. However, there is no easily available research-informed guidance on what self-confidence means for the professional teacher. This study uses the analytic technique of Concept Analysis to review psychology and education literatures to provide a 'take-home' message for teachers. The review identifies conceptual artefacts (ideas, theories, concepts which explain, connect, predict or apply knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 106 publications
0
21
0
2
Order By: Relevance
“…In addition, students who set proximal goals develop stronger academic confidence than those who set distal goals, as the former allows more opportunities to recognize growing expertise (Bandura & Schunk, ). It has also been suggested that confidence may be developed through interventions targeting emotional well‐being, pedagogy that promotes the active and voluntary sharing of knowledge, and educational interventions that are designed to improve attainment in specific curricular domains (e.g., see Maclellan, ). These approaches may support teachers to develop this attribute among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, students who set proximal goals develop stronger academic confidence than those who set distal goals, as the former allows more opportunities to recognize growing expertise (Bandura & Schunk, ). It has also been suggested that confidence may be developed through interventions targeting emotional well‐being, pedagogy that promotes the active and voluntary sharing of knowledge, and educational interventions that are designed to improve attainment in specific curricular domains (e.g., see Maclellan, ). These approaches may support teachers to develop this attribute among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…There is also some research which indicates a positive relationship between pupils feeling good and achieving well at school (Maclellan 2014), as well as research indicating a strong correlation between pupils' sense of confidence and their outcomes (Stankov, Morony, and Lee 2014). These projects suggest that pupils' confidence can be increased by the successful, autonomous use of metacognitive strategies, which is perhaps unsurprising.…”
Section: Metacognition In Historical and Policy Contextsmentioning
confidence: 99%
“…Studies found interventions putting students in a growth-mindset reversed trends for declining grades (Blackwell, Trzesniewski and Dweck 2007;Good, Aronson and Inzlicht 2003). How teachers view students impacts upon students' selfimage, view of themselves as students (Allen 2003), motivation (Pollard et al 2001) and self-confidence (Maclellan 2014).…”
Section: Student Beliefsmentioning
confidence: 99%